Body composition in Japanese patients with psychiatric disorders: A cross‐sectional study - Taro Kishi; Makoto Okuya; Kenji Sakuma; Yohei Otaka; Eiichi Saitoh; Nakao Iwata (Neuropsychopharmacology Reports, 2021)
Abstract Aim This study aimed to investigate body composition in Japanese patients with psychiatric disorders. Methods A cross‐sectional study was conducted to assess the body composition in Japanese patients with psychiatric disorders and healthy controls. InBody470 was used to measure the body composition of the participants. For the primary analysis, measures of body composition between patients and healthy controls were compared. Moreover, the following patient subgroups were also compared with the healthy controls: (a) patients with psychotic disorders only, (b) patients with mood disorders only, (c) patients receiving antipsychotics, (d) patients receiving conventional mood stabilizers, (e) patients receiving antidepressants only but not any antipsychotics and/or mood stabilizers, and (f) patients receiving hypnotics/anxiolytics. Results This study included 205 individuals (105 patients and 100 healthy controls). It was found that patients had a significantly higher body mass index, waist‐hip ratio, body fat mass, and percent body fat compared with the healthy controls. Moreover, significant differences were noted in the waist‐hip ratio, body fat mass, and percent body fat between all patient subgroups other than patients receiving conventional mood stabilizers subgroup and healthy controls. Conclusion This is the first cross‐sectional study to examine body composition in Japanese patients with psychiatric disorders. No difference in the skeletal muscle volume was noted although patients had higher body fat than healthy controls. A longitudinal and large cohort study in the future, controlling for medication and diagnosis, will need to determine why body fat is increased in Japanese patients with psychiatric disorders.